Proteomic profiling of the molecular targets of interactions of the mastoparan peptide Protopolybia MP-III at the level of endosomal membranes from rat mast cells - dos Santos, Lucilene Delazari [UNESP]; Aparecido dos Santos Pinto, Jose Roberto [UNESP]; da Silva Menegasso, Anally Ribeiro [UNESP]; Saidemberg, Daniel Menezes [UNESP]; Caviquioli Garcia, Ana Maria [UNESP]; Palma, Mario Sergio [UNESP] (Wiley-Blackwell, 2012)
It is well known that the activation of mast cells due to the binding of mastoparan to the Ga subunit of trimeric G proteins involves exocytosis regulation. However, experimental evidence in the literature indicates that mastoparan can also activate certain regulatory targets of exocytosis at the level of the mast cell endosomal membranes that have not yet been identified. Therefore, the aim of the present investigation was the proteomic identification of these targets. To achieve these objectives, mast cells were activated by the peptide Protopolybia MP-III, and the proteins of the endosomal membranes were converted to proteoliposomes using sonication. Proteins were separated from one another by affinity chromatography using proteoliposomes as analytes and Protopolybia MP III-immobilized Sepharose 4B resin as the ligand. This experimental approach, which used SDS-PAGE, in-gel trypsin digestion and proteomic analysis, permitted the identification of five endosomal proteins: Rho GTPase Cdc 42 and exocyst complex component 7 as components of the Ca2+-independent FceRI-mediated exocytosis pathway, synaptosomal-associated protein 29, and GTP-binding protein Rab3D as components of the Ca2+-dependent FceRI-mediated exocytosis pathway and Ras-related protein M-Ras, a protein that is related to the mediation of cell shaping and proliferation following exocytosis. The identification of the five proteins as targets of mastoparans may contribute in the near future to the use of this family of peptides as novel tools for dissecting the mechanism of exocytosis in mast cells.
Keywords: Affinity chromatography; Animal proteomics; Exocytosis; Mass spectrometry; Proteoliposomes